Hubungan Peran Orang Tua Sebagai Motivator terhadap Prestasi Belajar Siswa Kelas II SD - Amir Pada; Mutmainnah Mutmainnah; nursiah nursiah (Universtas Negeri Makassar, 2022)
The problem in this study relates to the description of the role of parents as a motivator to determine its relationship with the learning achievement of class II students of SD Inpres Pai 1, Biringkanaya District, Makassar City. This study aims to determine the description of the role of parents as motivators and a description of the learning achievement of second grade students at SD Inpres Pai 1, Biringkanaya District, Makassar City, and to find out whether there is a relationship between the role of parents as motivators for student achievement in class II at SD Inpres Pai 1, Biringkanaya District, Kota Makassar. This research is a descriptive correlational quantitative research. The population in this study were second grade students of SD Inpres Pai 1, Biringkanaya District, Makassar City, totaling 68 students. The research sample was class II students, totaling 34 students. The technique of data collection is done by using questionnaire and documentation technique, while the data analysis technique is using Product Moment correlation analysis technique. The results showed that (1) the role of parents as motivators was in the high category (2) student achievement was in the high category, and (3) there was a significant relationship between the role of parents as motivators and the learning achievement of grade II students at SD Inpres Pai. 1 Biringkanaya District, Makassar City.